Comunicación oral en la transmisión de conocimientos ancestrales de los Yachaks en la comunidad El Castillo del cantón Guaranda, año 2024 - Pilatasig Caiza, Kevin Jose (2025)
This research focuses on the crucial role that oral communication plays in the transmission of ancestral knowledge among the Yachaks in the community of El Castillo, located in the canton of Guaranda, during the year 2024. The Yachaks, who are considered sages and spiritual guides of the Andean Wuaranka culture, have maintained and shared their wisdom through oral tradition, an essential teaching method in Indigenous communities. The study adopts a qualitative approach, conducting in depth interviews with the Yachaks and community members, as well as participatory observation to understand how knowledge about ancestral medicine, rituals, and spiritual practices is transmitted from generation to generation. It also analyzes how sociocultural and technological changes affect the preservation of these traditions. The findings indicate that oral communication remains the primary means of teaching, although it faces challenges due to migration, globalization, and declining interest among younger generations. Strategies are proposed to strengthen the transmission of this knowledge, such as the creation of community learning spaces and the use of digital tools to complement this process.